Facilitating Trade and Structural Adjustment the Philippines Experience in Non-Member Economies - Antonio, Emilio (OECD Trade Policy Papers, 2007)
This paper is the second of four country case studies which is a part of a broader research programme addressing trade and structural adjustment issues in non-member economies which was conducted as a follow-up to Trade and Structural Adjustment: Embracing Globalisation (OECD, 2005) which identified policies for successful trade-related structural adjustment. This paper studies the trade liberalisation experience of the Philippines from the 1980s. The report consists of 7 main parts; Part 1 provides the introduction, part 2 looks at the economic policies in the Philippines from the 1970s, and part 3 takes a general look at the general structure of the economy. Part 4 takes a closer look at the trade liberalisation in the Philippines which was implemented in three phases, (1) initial trade reforms (1981-88), (2) second phase (1991-93) and (3) third phase (1994-96). Part 5 takes an overview of the structural adjustments which took place in manufacturing and agriculture, with Part 6 taking a closer look at four sectors, electronics, food processing, cement, and business process outsourcing sectors. Part 7 concludes with lessons learnt and opportunities and challenges for further liberalisation. Despite considerable liberalisation including in trade policy since the 1980s, the Philippines economy posted only lacklustre performance initially. After a growth period in the 1990s and the Asian crisis, it is only in the recent past that some of the reforms are starting to pay off. The importance of a stable political and macroecnomic environment, need for appropriate exchange rates, need for early elimination of quantitative restrictions in trade reform, early deregulation on FDI are some of the lessons learnt. While challenges remain, better results are expected in the future if complemented with further reforms